2020
DOI: 10.7150/ijbs.44943
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical tumor microenvironment and transduction: cytoskeleton mediates cancer cell invasion and metastasis

Abstract: Metastasis is a complicated, multistep process that is responsible for over 90% of cancer-related death. Metastatic disease or the movement of cancer cells from one site to another requires dramatic remodeling of the cytoskeleton. The regulation of cancer cell migration is determined not only by biochemical factors in the microenvironment but also by the biomechanical contextual information provided by the extracellular matrix (ECM). The responses of the cytoskeleton to chemical signals are well characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(82 citation statements)
references
References 192 publications
(197 reference statements)
0
82
0
Order By: Relevance
“…Previous studies also found that TRPV4 regulated the thickness of F-actin stress fibers and the reinforcement of focal adhesion contacted through TRPV4-induced cation/calcium influx 50 . Many signaling pathways have been reported to have an impact on cytoskeletal regulation through metastasis including RhoA/ROCK, PI3K/mTOR, and Hippo pathway 51 . In this research, we focused on the RhoA/ROCK1 pathway and cytoskeletal regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also found that TRPV4 regulated the thickness of F-actin stress fibers and the reinforcement of focal adhesion contacted through TRPV4-induced cation/calcium influx 50 . Many signaling pathways have been reported to have an impact on cytoskeletal regulation through metastasis including RhoA/ROCK, PI3K/mTOR, and Hippo pathway 51 . In this research, we focused on the RhoA/ROCK1 pathway and cytoskeletal regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The functional consequences of oncogenic mutations of KRAS , p53 and APC in CRC involve marked alterations of the actin cytoskeleton [ 13 , 14 , 15 ]. Furthermore, the abnormal structure and dynamics of actin filaments could be induced by altered physical properties and increased proinflammatory signaling of the tumor stroma [ 12 , 16 , 17 , 18 ]. Such a complex interplay between autonomous and extrinsic factors in the cell creates significant challenges for understanding the mechanisms and functional consequences of the altered actin cytoskeletal organization in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…In these processes, cytoskeleton remodeling plays an important role [ 136 ]. External signals are received from mechanosensors and translated into internal responses by the cytoskeleton, activating different pathways such as the Hippo pathway, the focal adhesion kinases (FAK), GTP-binding protein RhoA, and JAK/STAT [ 137 ].…”
Section: Inter-organellar Communications In Cancer Cellsmentioning
confidence: 99%